Consumer's Surplus, and Discriminating Monopoly - Houghton, Roy (Review of Economic Studies, 1958)
Journal Article Consumer's Surplus, and Discriminating Monopoly Get access Roy Houghton Roy Houghton Sheffield Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 1, October 1958, Pages 72–74, https://doi.org/10.2307/2295862 Published: 01 October 1958